Der wissenschaftliche Artikel in der germanistischen Linguistik als Modell für den Unterricht wissenschaftlichen Schreibens: Ergebnisse einer Pilotstudie - Huemer, Birgit (Linguistik Online, 2016)
Similar structures in research articles of different disciplines indicate that the research article can be qualified as a genre across disciplinary borders. In spite of these structural similarities, which are constitutive for a genre, there are linguistic varieties that can be found in research articles of several disciplines relevant to be pointed out when teaching academic writing at the university. Little research has been conducted so far on linguistic varieties within subcategories of a discipline, because it is assumed that linguistic varieties within the genre research article are discipline-specific and therefore can only be found across disciplines. This article will present the results of a pilot study in which linguistic varieties within the discipline German linguistics have been researched. 14 introductions to research articles within this field have been selected in order to analyse their macro structure in detail. The data has been taken from a high rated journal in the field of German linguistics called Zeitschrift für germanistische Linguistik (ZGL 2014) in which the most important articles that have been published in the year before are promoted. The study shows that the macro structure of the research articles’ introductions are essentially determined by the research question and the research method, which vary within this discipline. This result is particularly relevant for the teaching of academic writing, because it offers an alternative approach to support the writing process oriented towards the core of every research: which is to formulate a research question and to choose an appropriate method rather than to strictly follow assumed disciplinary writing norms.